Is It More Effective to Prescribe a Proton Pump Inhibitor Separately before a Meal for the Eradication of Helicobacter pylori? - Gyu Won Lee; Jae Hyun Kim; Won Moon; Seun Ja Park; Moo In Park; Sung Eun Kim; Hye Jung Kwon; Youn Jung Choi (Yong Chan Lee, 2018)
Background/Aims: The current standard regimen for the treatment of Helicobacter pylori infection is a combination of a proton pump inhibitor (PPI), amoxicillin, and clarithromycin. The aim of this study was to determine the effectiveness of PPIs taken separately before a meal for the treatment of H. pylori infection. Materials and Methods: This retrospective study included 160 patients who were tested positive for rapid urease in Kosin Unversity Gospel Hospital between January 2008 and December 2012. The patients were divided into two groups (n=80 in each group) based on the method of administration of the H. pylori triple therapy. Group A took a PPI before a meal and amoxicillin and clarithromycin after a meal. Group B took all three medications together after a meal. The 13C-urea breath test was performed after 4 weeks to assess the eradication of H. pylori. Results: H. pylori was eradicated in 58/80 (72.5%) patients in group A and 60/80 (75.0%) patients in group B, with no significant difference between the groups (P=0.719). Adverse effects occurred in 4 patients of group A and 7 patients of group B (5.0% and 8.8%, respectively); however, the difference between the groups was not significant (P=0.232). Conclusions: Administration of all medicines at once after a meal may be the better prescription for treatment, considering patient convenience and improved likelihood of compliance.